Ovos de resistência de cladóceros e sua contribuição para a diversidade específica do zooplâncton em uma lagoa da planície de inundação do alto rio Paraná. - Palazzo, Fabiana (2006)
Zooplankton produces resting eggs and diapause stages as strategies to promote its survival in the environment during periods of adverse conditions, and consequently allow the community diversity. The main aim of this study is to investigate these eggs contribution, presents in the bottom from an isolated lagoon in the upper Paraná river floodplain, for cladoceran diversity. We predict that species proceeding from eggs hatching do not occur in the plankton of the lagoon. Bottom samples were collected at six sampling sites in the Osmar lagoon banks, in September 2004 and June, July, August and September 2005, using a corer sampler. Zooplankton samplings were carried out in the pelagic region using a motorized pump (1000 L) and plankton net (68 µm). At the same time, pH, water temperature (°C), electric conductivity (µS.cm-1) and dissolved oxygen (mg.L-1) were measured. In laboratory, the resting eggs were counted, photographed and stored in individuals plastic flasks, containing distilled water and maintained under constant temperature (25 ± 2°C) and photoperiod (12 h). Resting eggs were examined daily until hatching. Higher abundances of these eggs were observed in July, when lower values of temperature and electric conductivity and higher values of dissolved oxygen and pH were verified. ANOVA results showed that the abundance mean was significantly different among months. From resting eggs, Ceriodaphnia reticulata, Macrothrix spinosa, Ilyocryptus spinifer, Ephemeroporus tridentatus and Diaphanosoma sp. hatched out although they were not registered in the plankton samples. C. reticulata was registered in the first time on this floodplain. These results corroborated the hypothesis that resting eggs contribute for zooplankton diversity in the lagoon.